Evaluation of Omega-3 fatty acids in management of trigeminal neuralgia - Balwinder Singh; Ramandeep S Narang; Kirandeep Kaur; Soheyl Sheikh; Jasjeet K Narang (Wolters Kluwer Medknow Publications, 2018)
Background: Trigeminal neuralgic (TN) pain has been known as the world's worst pain. Omega-3 fatty acids have been recently studied extensively in neuralgic pain. Carbamazepine has been known to be the first drug of choice in treating TN pain. In the present study, the potential benefits of omega-3 fatty acids in addition to the carbamazepine were assessed. Objective: The objective of the study was to evaluate the role of omega-3 fatty acids in the neuralgic pain along with carbamazepine in treating neuralgic pain. Materials and Methods: The present study was undertaken on 114 patients with TN pain. The patients were divided in two groups. The group I consisted of patients who were on carbamazepine only, and group II comprised patients who were on carbamazepine and omega-3 fatty acids. The pain was assessed using Brief Pain Inventory questionnaire, which is the most widely used questionnaire for chronic pain. The patients were evaluated on the day of reporting and on subsequent follow-up at 2 weeks, 6 weeks, and 15 weeks interval. The data obtained was subjected to statistical analysis to assess the additional benefits of omega-3 fatty acids in TN pain. Results: The results obtained showed that the intensity of pain reduction and life quality was better in patients receiving carbamazepine and omega-3 fatty acids by the end of the 15th week compared to the patients receiving carbamazepine alone. Conclusion: The present study demonstrates the reduction in neuropathic pain on long-term usage of omega-3 fatty acids, signifying that omega-3 fatty acids may offer better relief in neuralgic pain.